Positive electrode active material and battery
By using positive electrode active material particles with spherical standard deviation (Z) ≥ 0.018, combined with the mixed particle structure of surface coating and no coating, the problem of the cathode active material particles rupture during the charge and discharge cycle of the battery is solved, and the durability and capacity stability of the battery are improved.
Patent Information
- Application Number
- CN202411310358.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-09-19
- Publication Date
- 2025-04-29
AI Technical Summary
During the charging and discharging cycle of existing batteries, due to the rupture of the positive electrode active material particles, the battery durability is reduced and the battery capacity continues to decrease.
The positive electrode active material particles with high spherical standard deviation (Z) are used, and the spherical standard deviation (Z) is ≥0.018. By adding a cladding on the particle surface or a mixed particle structure without cladding, the fillability between particles is improved and the possibility of particle fracture is reduced.
It effectively inhibits the rupture of the positive electrode active material particles, improves the durability of the battery, and slows down the battery capacity.
Smart Images

Figure CN119905572A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a positive electrode active material and a battery. Background Art
[0002] Conventionally, as a positive electrode active material for a battery having excellent resistance characteristics, a positive electrode active material to which various additive elements are added is used. In addition, in such a positive electrode active material for a battery, the shape of the particles of the positive electrode active material is controlled.
[0003] For example, Japanese Patent Application Laid-Open No. 2014-139128 discloses a lithium-manganese composite oxide having an average minor axis of 0.08 μm to 0.8 μm, an average major axis of 2 μm to 10 μm, and an average aspect ratio of 8 to 80. Summary of the invention
[0004] In the past, the positive electrode active material was pressed to fix the positive electrode active material when forming the positive electrode active material layer in the battery. However, if the positive electrode active material is pressed, a strong force is locally applied to the particles of the positive electrode active material, and the particles sometimes break. As a result, the durability of the battery is sometimes reduced, for example, the battery capacity continues to decrease after repeated charge and discharge cycles. Therefore, there is a demand for a battery in which the breakage of particles in a positive electrode active material is suppressed and, as a result, the battery has high durability.
[0005] The present disclosure has been made in view of the above circumstances, and an object of the present disclosure is to provide a positive electrode active material in which cracking of positive electrode active material particles is suppressed, and a battery having high durability.
[0006] Means for solving the above-mentioned problems include the following aspects. <1> A positive electrode active material comprising Li x Ni a Co b Mn c M d O y The composition of the positive electrode active material particles is shown in FIG. The sphericity standard deviation (Z) of the positive electrode active material particles is Z≥0.018. (In the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, 0≤d≤0.1, a+b+c+d=1.0, 1.5≤y≤2.1, and M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn). <2> according to <1> The positive electrode active material, wherein the sphericity standard deviation (Z) is 0.090≤Z≤0.800. <3> according to <1> The positive electrode active material comprises: a first active material particle having a coating on the surface, the coating containing a compound of the element represented by the M; and a second active material particle not having the coating on the surface. <4> A battery having <1> to <3> The positive electrode active material according to any one of the above.
[0007] According to the present disclosure, a positive electrode active material in which cracking of positive electrode active material particles is suppressed, and a battery having high durability are provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, in which like reference numerals represent like elements. Figure 1 This is a schematic cross-sectional view showing an example of a positive electrode active material according to an embodiment of the present disclosure. Figure 2 This is a schematic cross-sectional view showing a conventional positive electrode active material layer. Figure 3 This is a schematic cross-sectional view showing a state in which a conventional positive electrode active material layer is pressed. DETAILED DESCRIPTION
[0009] <Positive Electrode Active Material> The positive electrode active material according to the embodiment of the present disclosure includes a Li x Ni a Co b Mn c M d O y The positive electrode active material particles of the composition represented have a sphericity standard deviation (Z) of Z≥0.018 (in the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, 0≤d≤0.1, a+b+c+d=1.0, 1.5≤y≤2.1, and M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn).
[0010] According to the positive electrode active material according to the embodiment of the present disclosure, breakage of particles is suppressed, and when the positive electrode active material is used in a battery, the durability of the battery can be improved.
[0011] In the past, when forming the positive electrode active material layer used in the battery, the positive electrode active material was pressed (pressurized) to fix it. However, if the positive electrode active material is pressed, a strong force will be locally applied to the particles of the positive electrode active material, and sometimes the particles will break, and as a result, the durability of the battery will sometimes decrease (for example, the battery capacity continues to decrease after repeated charge and discharge cycles). It can be considered that this is because the standard deviation (Z) of the sphericity of particles in the previous positive electrode active material is relatively low (specifically, Z is less than 0.018). The standard deviation (Z) of the sphericity of particles in the positive electrode active material is relatively low, indicating that the sphericity of the particles of the positive electrode active material is consistent. If the sphericity of the particles of the positive electrode active material on the collector is consistent, the gaps between the particles of the positive electrode active material become larger, that is, the filling property becomes lower. If the positive electrode active material is pressed in a state where the gaps between the particles are large like this, a stronger force will be locally applied to the particles, and the positive electrode active material particles will rupture. In addition, it is believed that in a battery having ruptured positive electrode active material particles, the durability of the battery is deteriorated.
[0012] In contrast, in the positive electrode active material involved in the embodiment of the present disclosure, the standard deviation (Z) of the sphericity of the positive electrode active material particles is as high as 0.018 or more, that is, it indicates that the sphericity is inconsistent and contains positive electrode active material particles with different sphericities. By having positive electrode active material particles with different sphericities like this, the gaps between the particles of the positive electrode active material are filled, the gaps become smaller, that is, the filling property becomes higher. Moreover, even if the positive electrode active material in a state of high filling property is compressed, the situation where a strong force is locally applied to the particles is suppressed, and the occurrence of rupture in the positive electrode active material particles is suppressed. As a result, when the positive electrode active material is used in a battery, the durability of the battery can be improved (for example, the reduction in battery capacity after repeated charge and discharge cycles is suppressed).
[0013] Here, the positive electrode active material according to the embodiment of the present disclosure will be described with reference to the drawings by giving specific examples.
[0014] First, as the conventional positive electrode active material having a relatively low standard deviation (Z) of the sphericity of the particles (specifically, Z less than 0.018), for example, Figure 2 and Figure 3 The positive electrode active material is a particle of the shape shown. Figure 2 is a schematic cross-sectional view showing a conventional positive electrode active material layer. Figure 3 This is a schematic cross-sectional view showing a state in which a conventional positive electrode active material layer is pressed. Figure 2The positive electrode active material layer 20 shown is formed by stacking positive electrode active material particles 20A on the current collector 4. The positive electrode active material particles 20A are active material particles having a coating 220 on the surface, and the coating 220 contains a compound of an element represented by the aforementioned M (hereinafter also referred to as "M element"). The positive electrode active material particles 20A contained in the positive electrode active material layer 20 are all active material particles having a coating 220 containing a compound containing the M element on the surface, and the sphericity standard deviation (Z) of the positive electrode active material particles 20A is low, less than 0.018. In the positive electrode active material layer 20 containing only the positive electrode active material particles 20A having a low sphericity standard deviation (Z) as active materials, Figure 2 As shown in FIG. 1 , the gaps between the positive electrode active material particles 20A become larger. Figure 3 As shown, when the positive electrode active material layer 20 is pressed (pressurized) in the direction of arrow A, a strong force is locally applied to the positive electrode active material layer 20, and the positive electrode active material particles 20A may be broken 6.
[0015] On the other hand, an example of the positive electrode active material according to the embodiment of the present disclosure is shown in Figure 1 . Figure 1 This is a schematic cross-sectional view showing an example of a positive electrode active material according to an embodiment of the present disclosure. Figure 1 The positive electrode active material layer 2 shown is formed by stacking the first active material particles 2A and the second active material particles 2B on the current collector 4. The first active material particles 2A are active material particles having a coating 22 on the surface, and the coating 22 contains a compound of the element (M element) represented by the above-mentioned M, and the second active material particles 2B are active material particles without the coating 22 on the surface. The active material contained in the positive electrode active material layer 2 (that is, the first active material particles 20A and the second active material particles 20B) is a mixture of particles having the coating 22 on the surface and particles not having the coating 22 on the surface, and the sphericity standard deviation (Z) of the active material particles is high (specifically, 0.018 or more). In the positive electrode active material layer 2 including active material particles having a high sphericity standard deviation (Z), as Figure 1 As shown, the gaps between the active material particles become smaller. Therefore, even if the positive electrode active material layer 2 is pressed (pressurized), a strong force is prevented from being locally applied to the active material particles, and cracks are prevented from occurring in the active material (that is, the first active material particles 20A and the second active material particles 20B).
[0016] Next, the positive electrode active material according to the embodiment of the present disclosure will be described in detail.
[0017] (composition) The positive electrode active material according to the embodiment of the present disclosure includes a Li x Ni a Co b Mn c M d O y Positive electrode active material particles of a composition represented by (in the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, 0≤d≤0.1, a+b+c+d=1.0, 1.5≤y≤2.1, and M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn).
[0018] In the above composition, the ratio x of Li is 0.1 to 1.5, preferably 0.3 to 1.4, and more preferably 0.5 to 1.2. The ratio a of Ni is 0.5 or more and 1.0 or less, preferably 0.6 or more and 0.9 or less, and more preferably 0.7 or more and 0.8 or less. The ratio b of Co is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2. The ratio c of Mn is 0 to 0.3, preferably 0 to 0.2, and more preferably 0.1 to 0.2. The ratio d of M is 0 or more and 0.1 or less, preferably 0.01 or more and 0.09 or less, and more preferably 0.03 or more and 0.07 or less. In addition, the total ratio (a+b+c+d) of Ni, Co, Mn and M is 1.0. The ratio y of O is 1.5 or more and 2.1 or less, preferably 1.7 or more and 2.1 or less, and more preferably 1.9 or more and 2.0 or less.
[0019] (Standard deviation of sphericity (Z)) In the positive electrode active material according to the embodiment of the present disclosure, the sphericity standard deviation (Z) of the positive electrode active material particles is Z≥0.018. By setting the sphericity standard deviation (Z) to Z≥0.018, cracking in the positive electrode active material particles is suppressed, and when the positive electrode active material is used in a battery, the durability of the battery can be improved. From the viewpoint of suppressing the breakage of the positive electrode active material particles, the sphericity standard deviation (Z) of the positive electrode active material particles is preferably Z ≥ 0.090, and more preferably Z ≥ 0.100. The upper limit of the sphericity standard deviation (Z) of the positive electrode active material particles is not particularly limited, but is preferably Z≤0.800, more preferably Z≤0.650, from the viewpoint of improving the function as a positive electrode.
[0020] [Determination of sphericity standard deviation (Z)] The sphericity standard deviation (Z) of the positive electrode active material particles in the positive electrode active material is measured by the following method. First, for the positive electrode active material, an image is obtained using a scanning electron microscope (SEM, 5000-20000 times), and the particle analysis software of Explorer4 (Kyoto Trading Co., Ltd.) is used to calculate the true sphericity of the particles in the image. In addition, it is repeated until the true sphericity data of 1000 particles can be obtained. Next, the standard deviation is calculated based on the true sphericity calculated for 1000 particles, and the sphericity standard deviation (Z) is obtained.
[0021] A positive electrode active material having a sphericity standard deviation (Z) of Z ≥ 0.018 (that is, a positive electrode active material having a high sphericity standard deviation (Z)) can be prepared, for example, by the following method: (1) A method for obtaining a positive electrode active material by controlling the production method of active material particles to produce active material particles having a wide distribution of sphericity (that is, having various sphericities); (2) A method of preparing two or more types of active material particles having different sphericity (average sphericity), and then mixing the two or more types of active material particles to obtain a positive electrode active material.
[0022] Here, an example is given to illustrate the case where the positive electrode active material involved in the embodiment of the present disclosure is obtained using the above-mentioned method (2) (a method in which two or more active material particles with different sphericity (average sphericity) are prepared and then the two or more active material particles are mixed to obtain a positive electrode active material).
[0023] (First Active Material Particles and Second Active Material Particles) The positive electrode active material involved in the embodiment of the present disclosure is preferably, for example, the following positive electrode active material, which has: a first active material particle having a coating on the surface, the coating containing a compound of an element represented by M (M element); and a second active material particle not having the coating on the surface. A positive electrode active material having first active material particles having a coating of a compound containing an M element on the surface and second active material particles having no coating on the surface, for example, Figure 1 The positive electrode active material layer 2 shown in FIG. Figure 1As shown, the first active material particle 2A having the coating 22 containing the compound of the element M on the surface has an elliptical shape due to the presence of the coating 22 on the surface, while the second active material particle 2B having no coating 22 on the surface has a shape close to a sphere. Therefore, the sphericity standard deviation (Z) of the positive electrode active material as a whole becomes larger.
[0024] Therefore, from the perspective of easily controlling the sphericity standard deviation (Z) within the aforementioned range and, as a result, suppressing the breakage of the positive electrode active material particles, the positive electrode active material involved in the embodiment of the present disclosure is preferably the following positive electrode active material, which comprises: a first active material particle having a coating on the surface, the coating containing a compound of an element represented by M (M element); and a second active material particle not having the coating on the surface.
[0025] In addition, when the positive electrode active material has first active material particles with a coating on the surface and second active material particles without a coating on the surface, the mass ratio of the first active material particles to the second active material particles (first active material particles / second active material particles (mass %)) is preferably 10 mass % to 90 mass %, more preferably 20 mass % to 80 mass %, and further preferably 40 mass % to 60 mass %.
[0026] Furthermore, in the case where the positive electrode active material includes first active material particles having a coating on the surface and second active material particles having no coating on the surface, the composition of each particle will be described. The first active material particle having a coating on the surface preferably has a Li x1 Ni a1 Co b1 Mn c1 M d1 O y1 Represents a composition (in the composition of the first active material particles, 0.1≤x1≤1.5, 0.5≤a1≤1.0, 0≤b1≤0.3, 0≤c1≤0.3, 0≤d1≤0.1, a1+b1+c1+d1=1.0, 1.5≤y1≤2.1, and M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn).
[0027] The second active material particles without a coating on the surface preferably have a Li x2 Ni a2 Co b2 Mn c2 O y2The composition represented by (in the composition of the second active material particles, 0.1≤x2≤1.5, 0.5≤a2≤1.0, 0≤b2≤0.3, 0≤c2≤0.3, a2+b2+c2=1.0, 1.5≤y2≤2.1).
[0028] in addition, Figure 1 , a positive electrode active material having two types of active material particles, a first active material particle 2A having a coating 22 containing a compound of an element M on the surface and a second active material particle 2B having no coating 22 on the surface, is shown, but the present disclosure is not limited to this mode. For example, in addition to the first active material particle and the second active material particle, an active material particle having a sphericity (average sphericity) different from that of the first active material particle and the second active material particle may be included, that is, three or more active material particles having different sphericities (average sphericity) may be included.
[0029] (Method for producing positive electrode active material) Here, an example is given to illustrate a method for manufacturing a positive electrode active material according to an embodiment of the present disclosure. As an example, a method for manufacturing a positive electrode active material having a first active material particle having a coating containing a compound of an M element on the surface and a second active material particle having no coating on the surface is described.
[0030] The positive electrode active material including the first active material particles and the second active material particles can be produced, for example, by separately preparing the first active material particles and the second active material particles and then mixing the two particles.
[0031] Preparation of the second active material particles without coating First, a method for producing the second active material particles having no coating on the surface will be described. The second active material particles can be produced, for example, through the following steps (1) to (5). (1) Step of preparing a solution in which raw materials containing Ni, Co, and Mn are dissolved (raw material dissolution) (2) Adding the solution to an alkaline solution to precipitate the hydroxide (crystallization) (3) A step of collecting a precipitate from the alkaline solution (4) A step of mixing the precipitate with a raw material containing Li to obtain a mixture (Li raw material addition) (5) Firing step of firing the mixture (firing) (In addition, M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn).
[0032] (1) Step of preparing a solution in which raw materials containing Ni, Co, and Mn are dissolved A solution in which a raw material containing Ni, a raw material containing Co, and a raw material containing Mn are dissolved is prepared. For example, a solution can be prepared by dissolving a raw material containing Ni, a raw material containing Co, and a raw material containing Mn in a solvent such as water. The concentration of the solution is preferably set in a range of, for example, 10 mass % to 40 mass %. As a ratio of Ni / Co / Mn, it is preferably set to a ratio of 1.0 / 0.8 to 1.2 / 0.8 to 1.2 (atm %) relative to Ni: 1.0.
[0033] Examples of raw materials containing Ni include sulfates such as NiSO 4 , examples of raw materials containing Co include sulfates such as CoSO 4 , and examples of raw materials containing Mn include sulfates such as MnSO 4 .
[0034] (2) Step of adding a solution to an alkaline solution to precipitate a hydroxide Next, the solution is added to the alkaline solution to precipitate the hydroxide. As a result, particles generated by the hydroxides containing Ni, Co and Mn are crystallized, and the particles are obtained as precipitates. In this step, for example, the alkaline solution in which the hydroxide is precipitated is controlled to a certain pH (for example, pH 10 to 12) while the solution and NH3 are added dropwise, so that the hydroxide of the transition metal is precipitated.
[0035] (3) Step of collecting precipitate from alkaline solution Next, the precipitate is collected from the alkaline solution. As a method for collecting particles of the precipitate, for example, filtering and water washing methods can be cited. The following method can be cited: first, the precipitate (particles) are taken out by filtering and then washed with water, and then the liquid after washing is filtered to take out the precipitate (particles). In addition, the precipitate (particles) after washing can also be dried.
[0036] (4) Step of mixing the precipitate with a raw material containing Li to obtain a mixture Next, the collected precipitate (particles) and a raw material containing Li are mixed to obtain a mixture. For example, the collected precipitate particles and the raw material containing Li can be mixed in a mortar. Examples of raw materials containing Li include Li 2 CO 3 and LiOH.
[0037] (5) Firing step of firing the mixture Next, the mixture of the collected precipitate (particles) and the raw material containing Li is fired. For example, the mixture can be fired in a firing furnace (muffle furnace, etc.). The firing conditions can be, for example, a temperature of 800°C to 1100°C, an oxygen atmosphere, and a time of 5 hours to 20 hours.
[0038] Furthermore, the fired mixture may be crushed to obtain a predetermined particle size. Examples of the crushing method include crushing with a pulverizer (eg, jet mill).
[0039] By going through the steps (1) to (5), second active material particles having no coating on the surface can be obtained.
[0040] Preparation of first active material particles with coating By changing the step (4) of mixing the precipitate and a raw material containing Li to obtain a mixture in the aforementioned “preparation of second active material particles without a coating” to the following step (4′) of mixing the precipitate, a raw material containing Li, and a raw material containing the M element to obtain a mixture”, the first active material particles can be prepared.
[0041] (4′) A step of mixing the precipitate, a raw material containing Li, and a raw material containing an M element to obtain a mixture Next, the collected precipitate (particles), a raw material containing Li, and a raw material containing the element M are mixed to obtain a mixture. For example, the collected precipitate particles, the raw material containing Li, and the raw material containing the element M can be mixed in a mortar. Examples of raw materials containing Li include Li 2 CO 3 and LiOH. As raw materials containing M (that is, at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn), oxides of each element (for example, Nb2O5, W2O3, SrO, Pr2O3 and La2O3) and hydroxides of each element (for example, H3BO4) can be cited.
[0042] Mixing of first active material particles and second active material particles Next, by mixing the obtained first active material particles and second active material particles, the positive electrode active material according to the embodiment of the present disclosure can be obtained.
[0043] In addition, in the description of the above-mentioned manufacturing method, a positive electrode active material having two kinds of active material particles, namely, a first active material particle having a coating containing a compound of an M element on the surface and a second active material particle having no coating on the surface, is shown, but the present disclosure is not limited to this mode. For example, in addition to the first active material particle and the second active material particle, an active material particle having a sphericity (average sphericity) different from that of the first active material particle and the second active material particle may be prepared, and these three active material particles may be mixed to obtain the positive electrode active material involved in the embodiment of the present disclosure.
[0044] <Battery> The battery according to the embodiment of the present disclosure includes the positive electrode active material according to the embodiment of the present disclosure. The battery includes, for example, a negative electrode, a positive electrode, a separator, and an electrolyte. The battery involved in the embodiment of the present disclosure may be a solid battery having a solid electrolyte, or a liquid battery having a liquid electrolyte, or a bipolar battery having a positive electrode active material layer and a negative electrode active material layer on both sides of a current collector having the functions of a positive electrode current collector and a negative electrode current collector. The battery according to the embodiment of the present disclosure may be a liquid-based battery further comprising an electrolyte solution, and a non-aqueous electrolyte solution is particularly preferred.
[0045] (use) Examples of uses of the battery include power sources for hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), and battery electric vehicles (BEV).
[0046] Hereinafter, the present disclosure will be described based on examples, but the present disclosure is not limited to these examples at all.
[0047] <Example 1> (Synthesis of positive electrode active material) The positive electrode active material was synthesized by the following method, which comprises active material particles A having Li x Ni a Co b Mn c O y The composition represented by x, a, b, c and y are the ratios shown in Table 1; and active material particles B having Li x Ni a Co b Mn c M d O y In the composition represented by , x, a, b, c, d, and y have the ratios shown in Table 1, and as the element represented by M (M element), the elements described in Table 1 were used.
[0048] (Synthesis of Active Material Particles A) ·Raw material solution NiSO4, CoSO4 and MnSO4 were dissolved in ion exchange water to obtain a raw material solution. The ratio of Ni / Co / Mn was 1 / 1 / 1 (atm%), and the concentration of the aqueous solution was 30 mass%.
[0049] ·Crystallization A certain amount of NH3 aqueous solution is placed in a reaction vessel, and nitrogen substitution is performed while stirring with a stirrer. NaOH is added to the reaction vessel to make the pH alkaline. Next, the raw material solution and NH3 are added dropwise while controlling the pH in the reaction vessel to a certain value (pH 10-12) to precipitate the transition metal hydroxide.
[0050] Washing, filtering, drying The precipitated transition metal hydroxide was taken out by filtration, ion exchange water was added and stirred with a spatula to disperse it, and then washed with water. Next, the liquid after washing with water is filtered to take out the transition metal hydroxide. Next, the filtered transition metal hydroxide was dried at 120° C. for 16 hours to evaporate water.
[0051] ·Li raw material mixing The dried transition metal hydroxide and Li2CO3 and LiOH as Li raw materials are mixed in a mortar.
[0052] ·Firing and crushing The mixture of the transition metal hydroxide and the Li raw material is fired in a firing furnace (muffle furnace) at 800° C. to 1100° C. in an oxygen atmosphere for 10 hours. Next, the fired mixture is pulverized by a pulverizer (jet mill) to a predetermined particle size. In this way, active material particles A are obtained.
[0053] (Synthesis of Active Material Particles B) Active material particles B were obtained by the same method as in (Synthesis of active material particles A) except that the step of "mixing the Li raw material" in the above (Synthesis of active material particles A) was changed to the following "mixing of the Li raw material and the M raw material".
[0054] · Mixing of Li raw materials and M raw materials The dried transition metal hydroxide, Li2CO3 and LiOH as Li raw materials, and H3BO4 as M raw material are mixed in a mortar.
[0055] (Mixing of Active Material Particles A and Active Material Particles B) The obtained active material particles A and active material particles B were mixed at the particle ratio A / B (mass ratio (mass %) of active material particles A to active material particles B) shown in Table 1, thereby obtaining a positive electrode active material of Example 1.
[0056] <Examples 2 to 5 and Example 7> The positive electrode active materials of each example were obtained in the same manner as in Example 1, except that the M raw material used in the synthesis of the active material particles B in Example 1 was changed from H3BO4 to Nb2O5 (Example 2), W2O3 (Example 3), SrO (Example 4), Pr2O3 (Example 5) and La2O3 (Example 7).
[0057] <Example 6 and Example 8> The positive electrode active materials of each example were obtained in the same manner as in Example 7 except that the particle ratio A / B (mass ratio (mass %) of active material particles A to active material particles B) in Example 7 was changed to the particle ratio described in Table 1.
[0058] <Comparative Example 1> The “active material particles A” synthesized in Example 1 were used as the positive electrode active material of Comparative Example 1.
[0059] <Comparative Example 2> The “active material particles B” synthesized in Example 2 were used as the positive electrode active material of Comparative Example 2.
[0060] <Comparative Example 3> The “active material particles B” synthesized in Example 3 were used as the positive electrode active material of Comparative Example 3.
[0061] In this embodiment, the method of synthesizing active material particles synthesized by adding M raw material and active material particles synthesized without adding M raw material as in Examples 1 to 8 and mixing these two active material particles to obtain a positive electrode active material is referred to as "synthesis method 1". In this example, the method of synthesizing active material particles without adding M raw material or synthesizing active material particles with adding M raw material as in Comparative Examples 1 to 3 and using them as positive electrode active material is referred to as "Synthesis Method 2".
[0062] [Determination of sphericity standard deviation (Z)] Regarding the positive electrode active materials obtained in Examples 1 to 8 and Comparative Examples 1 to 3, the sphericity standard deviation (Z) of the positive electrode active material particles was measured by the following method.
[0063] First, for the positive electrode active material, an image was obtained using SEM (5000-20000 times), and the particle analysis software of Explorer4 (Kyoto Trading Co., Ltd.) was used to calculate the true sphericity of the particles in the image. This was repeated until the true sphericity data of 1000 particles could be obtained. Next, the standard deviation was calculated based on the true sphericity calculated for 1000 particles to obtain the sphericity standard deviation (Z).
[0064] [Production of a single unit] A single body was prepared using the positive electrode active material obtained in each of the Examples and Comparative Examples. Monomer composition Winding cylinder Positive electrode composition: Positive electrode active material / acetylene black (conductive material) / polyvinylidene fluoride = 88 / 10 / 2 (mass %) Negative electrode composition: natural graphite / styrene-butadiene rubber (SBR) / carboxymethyl cellulose (CMC) Electrolyte composition: electrolyte = LiPF6 (1M), solvent = ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) = 3 / 4 / 3 (volume %)
[0065] Electrode production The positive electrode and the negative electrode were coated on the current collector using a film coater with a film thickness adjustment function (manufactured by Ohlgod Co., Ltd.), and dried at 80° C. for 5 minutes in a dryer to prepare a single body.
[0066] [Determination of resistance increase rate after cycling] For the monomers obtained in each embodiment and comparative example, the battery capacity was measured before and after cycling under the following test conditions. The results of the ratio of the battery capacity after cycling (capacity retention rate (%)) when the battery capacity before cycling is set to "100%" are shown in Table 1. The closer the capacity retention rate is to 100%, the better the battery characteristics can be said to be. Test conditions: charge and discharge were performed at 60°C, 2C rate, SOC 0% to 100%, and 300 cycles. [Table 1]
[0067] As shown in Table 1, in the positive electrode active materials of each embodiment having a sphericity standard deviation (Z) as high as 0.018 or more, the capacity retention rate after cycling is maintained higher than that of the positive electrode active materials of each comparative example having a sphericity standard deviation (Z) as low as less than 0.018.
Claims
1. A positive electrode active material comprising Li x Ni a Co b Mn c M d O y The composition of the positive electrode active material particles is shown in FIG. The sphericity standard deviation (Z) of the positive electrode active material particles is Z≥0.018, in, In the composition, 0.1≤x≤1.5, 0.5≤a≤1.0, 0≤b≤0.3, 0≤c≤0.3, 0≤d≤0.1, a+b+c+d=1.0, 1.5≤y≤2.1, and M represents at least one element selected from the group consisting of B, Nb, W, Sr, Pr, La, Ba, Mg, Al, Zr, Sc, Ti, Y, Hf and Sn.
2. The positive electrode active material according to claim 1, wherein The sphericity standard deviation (Z) is 0.090≤Z≤0.
800.
3. The positive electrode active material according to claim 1, wherein The method comprises: first active material particles having a coating on the surface thereof, the coating containing a compound of the element represented by the M; and second active material particles not having the coating on the surface thereof. 4 . A battery comprising the positive electrode active material according to claim 1 .
Citation Information
Patent Citations
Lithium manganese-based complex oxide
JP2014139128A